2012
DOI: 10.1128/aem.00465-12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Relative Humidity and Spraying Medium on UV Decontamination of Filters Loaded with Viral Aerosols

Abstract: Although respirators and filters are designed to prevent the spread of pathogenic aerosols, a stockpile shortage is anticipated during the next flu pandemic. Contact transfer and reaerosolization of collected microbes from used respirators are also a concern. An option to address these potential problems is UV irradiation, which inactivates microbes by dimerizing thymine/uracil in nucleic acids. The objective of this study was to determine the effects of transmission mode and environmental conditions on decont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 28 publications
3
49
0
Order By: Relevance
“…For MS2, Q␤, and X174, k values of 0.28, 0.44, and 2.02 cm 2 /mJ were calculated, respectively, and X174 showed the highest UV sensitivity among the studied viruses. This result is consistent with a study investigating loss of viral infectivity following UVC LED water and air disinfection in which X174 demonstrated higher sensitivity than MS2 (23,25,32,33). Dimerization of thymine in DNA and uracil in RNA by UVC irradiation occurred not to the same degree, because absorption spectra of the nucleotides showed different peak wavelengths.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For MS2, Q␤, and X174, k values of 0.28, 0.44, and 2.02 cm 2 /mJ were calculated, respectively, and X174 showed the highest UV sensitivity among the studied viruses. This result is consistent with a study investigating loss of viral infectivity following UVC LED water and air disinfection in which X174 demonstrated higher sensitivity than MS2 (23,25,32,33). Dimerization of thymine in DNA and uracil in RNA by UVC irradiation occurred not to the same degree, because absorption spectra of the nucleotides showed different peak wavelengths.…”
Section: Resultssupporting
confidence: 90%
“…Griffiths et al reported a 1.6-log reduction of MS2 by a heating, ventilation, and air conditioning (HVAC) system incorporating 6 UV lamps (no irradiation dose specified) (24). Also, an approximately 3-log reduction of MS2 dispersed in beef extract medium solution and artificial saliva occurred when treated with 7,200 mJ/cm 2 in an air disinfection system (25). Surviving populations and fitted curves for E. coli O157:H7, S. Typhimurium, L. monocytogenes, and S. aureus are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An added complication is that viruses are often damaged/inactivated during collection using air samplers, due to the stresses and forces acting upon them. 24,[28][29][30][31] To be able to evaluate and compare different methods for detecting viable viral aerosols, our first goal was to develop a system that could safely, efficiently, and consistently generate aerosolized influenza virus. The viral aerosol-generation system was coupled with a bioaerosol sampler for characterizing airborne particles associated with viable influenza viruses.…”
Section: Introductionmentioning
confidence: 99%
“…To better simulate the generation of virus aerosols from human saliva, several researchers have developed a recipe for making artificial saliva and have used it as a nebulizer suspension (10)(11)(12)(13). The same artificial saliva was later adopted by ASTM to evaluate the decontamination efficacy of air-permeable materials and surfaces challenged with bioaerosols (14,15).…”
mentioning
confidence: 99%